PHYTOTHERAPEUTIC POTENTIAL OF MEDICINAL PLANTS IN THE MANAGEMENT OF HYPERTENSION: A PHARMACOGNOSTIC REVIEW - MAHESHWARAN M; KAMARAJ R (The Bioscan, 2025)
Hypertension, being one of the major health issues in the world is not well controlled despite many pharmacological interventions because of side effects, cost, and poor compliance. The use of medicinal plants is known as phytotherapy and this has again become a subject of concern as far as the complementary and alternative methods of treatment of high blood pressure is concerned. This pharmacognostic review brings to the ethnomedical significance, bioactive constituents and the mechanism of different antihypertensive medicinal plants. Most of these plants have vasodilatory, diuretic, ACE-inhibitory, calcium blockers and antioxidant properties, which reflect the current areas of focus in pharmacology. Such plants have been used in the tradition of Ayurvedic, Traditional Chinese Medicine, and Persian Medicine systems in the treatment of hypertension. As Phyto therapeutic agents continue to have increased scientific evidence in their efficiency and safety, they portray great cost-effective, beneficial prospects in the enhancement of effective hypertension treatment worldwide as an accompaniment to conventional treatment.